2020
DOI: 10.3390/ma13183926
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Microstructure Evolution in Mo Thin Films without or with Cover Layers during Thermal-Cycling

Abstract: The intrinsic stress behavior and microstructure evolution of Molybdenum thin films were investigated to evaluate their applicability as a metallization in high temperature microelectronic devices. For this purpose, 100 nm thick Mo films were sputter-deposited without or with an AlN or SiO2 cover layer on thermally oxidized Si substrates. The samples were subjected to thermal cycling up to 900 °C in ultrahigh vacuum; meanwhile, the in-situ stress behavior was monitored by a laser based Multi-beam Optical Senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…More descriptions about the reasons for the selection of such barrier and cover layers systems are available in the previous studies. [1,2,5,8,12,26] The schematic views of the metallization systems used in this study are shown in Figure 1. It is worth mentioning that the Si substrate is not used in the real application and the reason for using it as a substrate in this study is the isotropic behavior of the Si [100] in the wafer plane (cubic anisotropy) which is more convenient for the strain-stress and creep calculations compared to an anisotropic piezoelectric material which is required to fabricate SAW sensors.…”
Section: Specimen Preparationmentioning
confidence: 99%
See 4 more Smart Citations
“…More descriptions about the reasons for the selection of such barrier and cover layers systems are available in the previous studies. [1,2,5,8,12,26] The schematic views of the metallization systems used in this study are shown in Figure 1. It is worth mentioning that the Si substrate is not used in the real application and the reason for using it as a substrate in this study is the isotropic behavior of the Si [100] in the wafer plane (cubic anisotropy) which is more convenient for the strain-stress and creep calculations compared to an anisotropic piezoelectric material which is required to fabricate SAW sensors.…”
Section: Specimen Preparationmentioning
confidence: 99%
“…Thin films consisting of pure molybdenum (Mo), molybdenumlanthanum oxide (MoLa), and ruthenium-aluminum (RuAl) are suggested metal films for electrodes of high-temperature (HT) surface acoustic wave (SAW) sensors based on our recent extensive researches on different multilayered thin film systems. [1][2][3][4][5][6][7][8][9][10] Despite the high performance temperature of the metallization systems made of these metals, they have characteristics such as low electrical resistivity and corrosion resistance, which make them a suitable choice for SAW sensor electrodes. [2,11,12] DOI: 10.1002/admt.202201979 HT-SAW sensors can be used for wireless sensing of temperature, pressure, and detection of gases, in turbine rotors, furnaces, ovens, etc., without any batteries or high sources of energy.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations